The effect of octreotide against oxidative damage in photosensitized conjunctiva and cornea of rabbits - Demir, Ü; Demir, T; Akpolat, N (Springer, 2005)
The purpose of this study was to determine the protective effect of octreotide against oxidative damage ill rabbit conjunctiva and cornea exposed to Ultraviolet radiation. Twenty rabbits weighing 2500-3000 g were used and we divided them into 4 groups With randomly selected 5 rabbits. Rabbits were exposed to 2 J/cm(2)/ h of ultraviolet A radiation (UVA) in the range 320-405 nm for 12 h per day for 90 days. Group 1 did not receive any treatment or UVA exposure (control group). Group 2 was only exposed to UVA radiation (UVA group). Group 3 received 8-methoxypsoralen and UVA (PUVA group). Group 4 was treated with 8-methoxypsoralen + UVA + octreotide (octreotide group). At the end of 90 days the rabbits were killed by decapitation and then eyes were enucleated. Both eyes of each rabbit were used for histopathologic evaluation. Histopathologic analysis of each group indicated that UVA group and PUVA group showed increasing edema (p < 0.01), inflammation (p < 0.05), Fibroblast proliferation (p < 0.05). dysplasia (p < 0.05), hyperchromasia (p<0.01) in the conjunctiva. Octreotide group had significant protective effect ill comparison with the UVA group and PUVA group. The UVA group and PUVA group showed increasing proliferation (p<0.01), dysplasia (p<0.01), hyperchromasia (p<0.01), pyknosis)<0.001) and parakeratosis (p < 0.01) in the corneal epithelium. Octreotide group showed similar results with control group. We conclude that octreotide which is considered as free radical scavenger protects the eye from the damaging effect of UV exposure.
Keywords: PUVA; ultraviolet A; octreotide; cornea; conjunctiva; antioxidants